Biogenesis and ceRNA role of circular RNAs in skeletal muscle myogenesis. (December 2019) - Yue, Binglin; Wang, Jian; Song, Chengchuang; Wu, Jiyao; Cao, Xiukai; Huang, Yongzheng; Lan, Xianyong; Lei, Chuzhao; Huang, Bizhi; Chen, Hong
Abstract: Circular RNAs (circRNAs) are novel endogenous non-coding RNAs that are generated by reverse-splicing of precursor mRNA derived from various genes in mammals. Despite low expression, recent studies have shown that circRNA plays an important role in skeletal muscle myogenesis with competing endogenous RNA (ceRNA) functions. However, the potential regulatory role of circRNAs and interactions with miRNAs remain largely unexplored, and the function of circRNAs as miRNA sponges is not yet generally accepted. In this review, we outline the biogenesis and ceRNA mechanisms of circRNAs as well as their involvement in skeletal muscle myogenesis and discuss the conflicting conclusions of recent circRNA-ceRNA studies.